Production of banana bunchy top virus (BBTV)-free plantain plants by in vitro culture - Tchatchambe, N.B.J.; Ibanda, N.; Adheka, G.; Onautshu, O.; Swennen, Rony L.; Dhed’a, D. (Academic Journals, 2020)
Banana Bunchy Top Disease (BBTD) caused by the Banana Bunchy Top Virus (BBTV) is one of the most important banana diseases in the Democratic Republic of Congo. This study focused on the production of BBTV-free plantain seedlings from infected banana plants. A total of 10 suckers from the French plantain Litete (Musa AAB) and the False Horn plantain Libanga Likale (Musa AAB) with advanced BBTD symptoms were collected. Meristematic apices excised from those suckers were cultured in vitro and subcultured five times. The presence of BBTV was evaluated by the Triple-Antibody Sandwich Enzyme-linked Immunosorbent Assay (TAS-ELISA). The BBTV was confirmed in all suckers prior to in vitro culture but 73.3% of Litete plantlets and 66.6% of Libanga Likale plantlets regenerated from meristematic tissues were virus-free. This indicates that in vitro culture is a simple tool to generate BBTV-free plantains.